Năng lực số, hiểu biết trí tuệ nhân tạo và khả năng có việc làm của sinh viên Việt Nam: Tổng quan hệ thống giai đoạn 2019-2025 - Võ Phương Uyên, Võ Phương Uyên; Lê Thị Thanh Tịnh, Lê Thị Thanh Tịnh (Tạp chí Giáo dục, 2026)
In the context of Vietnamese higher education being strongly impacted by digital transformation and the spread of artificial intelligence in the socioeconomic landscape, digital and AI competencies are increasingly seen as foundational to employability. The integration of AI competencies into the National Digital Competency Framework under Circular No. 02/2025 requires a systematic synthesis and evaluation of scientific evidence on the relationship between these competencies and the employability of university students. This article provides a systematic overview of 22 publications from 2019-2025 following the PRISMA methodology. The results show a rapid increase in research in recent years, primarily using cross-sectional quantitative designs. Relatively consistent aggregate evidence indicates a positive correlation between digital competence, AI literacy, and students’ career adaptability, entrepreneurial orientation, and job readiness, mediated by factors such as self-efficacy, innovation capacity, and professional identity. These findings clarify the mechanisms by which digital competence and AI impact employability, while also providing scientific justification for curriculum design and human resource development policy planning in the context of the digital economy.